Nanoimprint Lithography: Angle‐Insensitive and CMOS‐Compatible Subwavelength Color Printing (Advanced Optical Materials 11/2016). Issue 11 (16th November 2016) - Lee, Kyu‐Tae; Jang, Ji‐Yun; Park, Sang Jin; Ji, Chengang; Yang, Sung‐Mo; Guo, L. Jay; Park, Hui Joon
Abstract : Photonic nanostructures for a wide‐angle and complementary metal‐oxide semiconductor (CMOS)‐compatible structural color printing scheme, which eploite strong resonance effects in ultrathin subwavelength semiconductor gratings, are developed by H. J. Park and co‐workers. The proposed structural colors create distinctive colors with great homogeneity and high color saturation, which are easily tuned by varying the width of the subwavelength gratings, thereby enabling individual color pixels to be patterned via a one‐step fabrication process.